Electrochemical oxidation of fisetin: Studies related to its adsorption on glassy carbon electrodes - Maza, Eliana María (2012)
The electrochemical oxidation of fisetin (FIS) on glassy carbon (GC) electrodes is studied in 15% dimethyl sulfoxide (DMSO) +85% pH 4.00 and 7.00 buffer solutions by cyclic (CV) and square-wave (SWV) voltammetries. The first oxidation peak of FIS showed an adsorption/diffusion mixed control, when studies were performed in solutions in the presence of FIS. Therefore, the FIS adsorption on the GC electrode surface could be inferred from cyclic voltammograms recorded in supporting electrolyte solutions, where a quasi-reversible redox couple was defined at both pH values. These findings show that both the reactant and the product of the electrode process are adsorbed on the electrode surface, being the surface redox couple slightly better defined at pH 4.00 than 7.00. The Frumkin adsorption isotherm was the best to describe the specific interaction of FIS with GC electrodes, using a fitting procedure of experimental fractional surface coverage (θ) vs. FIS bulk concentration (cFIS). Moreover, we used the SWV to obtain a full characterization of the surface redox couple, applying the combination of the "quasi-reversible maximum" and the "splitting of the net voltammetric peak" methods. Values of (0.340 ± 0.003) V, 41 s-1, and (0.49 ± 0.04) were determined for the formal potential, the formal rate constant, and the anodic transfer coefficient, respectively.